Politolinguistik und Sprachkritik. Der öffentliche Diskurs um eine antisemitische Skandalrede als Beispiel für die Notwendigkeit einer kooperativ-kritischen Sprachwissenschaft - Roth, Kersten Sven (My University, 2006)
In the field of politics, there are public discourses on language but, although these discussions predominate the media over days and weeks, the general public will hardly notice that they are indeed debates on language. Above all, this has to do with the fact that linguistics, i.e. the science primarily responsible for these issues, hardly ever gets involved publically in these discussions that latently always also have an aspect of 'language criticism'. Based on the concrete example of a political scandal in the Federal Republic of Germany, the paper examines the way in which public discourse should be enriched by linguistic expertise and analyses the barriers that result from the self-conception of linguists and normally prevent them from getting involved. Ultimately, the paper presents the concept of cooperative-critical linguistics, which could be used to create the methodological basis for overcoming the public silence of political linguistics.
Keywords: Politolinguistik; Sprachkritik; Sprachberatung; Rhetorik; Diskurs